The history of punishment - Lyons, Lewis ([S.l.] : Grange Books, 2003)
Crime has always been apart of human society. It has been punished in many ways: from banishment to flogging and the death penalty. The History of Punishment reviews the penalties imposed in different cultures and times, addressing some intriguing questions: - Can imprisonment reform a criminal? - How can a punishment be made to fit the crime? - Who should decide what is fit punishment - should the victim have a say? This book takes a wide view of legally imposed punishment, looking at how it has been used in different societies (from Singapore to Pakistan) and different times (from ancient Greece right up to the present day). Alongside the clear and informative text, historical etchings and artworks as well as archive and press photographs offer a complete portrait of imprisonment, deportation, corporal punishment and the death penalty.
Keywords: Criminal law; Punishment